ANALISIS PEMILIHAN SUPPLIER BAHAN BAKU TEPUNG MENGGUNAKAN METODE ANALITYCAL HIERARCHY PRECESS (AHP) PADA PT TSABAT MANDIRI DI LAMPUNG TENGAH - Nani Septiana; Muhammad Iqbal Aldiansyah (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
Supplier selection is one of the important things in purchasing activities for the company. Supplier selection is a multi-criteria problem which includes quantitative and qualitative factors. One method that can be used for supplier selection is the AHP (Analitycal Hierarchy Process) method, which will develop a partnership relationship with flour suppliers. The problems that will be discussed in this study are: (1) How to determine the priority order of criteria and sub-criteria for selecting the best supplier in accordance with company conditions ?. (2) How to choose the best supplier in accordance with the conditions and capabilities of the company? The sample to be taken in conducting this research is the decision makers and those who know the supplier's performance. The sampling technique uses Judgment sampling because the AHP method requires dependence on a group of experts in accordance with the types of specialists involved in decision making.This study uses the AHP method and is assisted by MS Exel, from the assessment of the importance of criteria in the selection of suppliers to produce priority scale / weight as follows: priority I quality (0.440), priority II price (0.226), priority III delivery (0.142), priority IV services (0.099), priority V payments (0.091). From the results of the assessment of alternative importance levels in the selection of suppliers, the following priority / weight scales are: priority I bell (0.451), priority II gold rope (0.348), priority III supplier red badge (0.199).Based on the results of the analysis above, the advice that can be given is, if the company will develop a partnership relationship with the supplier, the company will prioritize choosing a bell supplier as a flour supplier in the company, because the bell supplier has the highest overall value. With this partnership, the performance of the supplier chain between suppliers and companies will be better and can accelerate the overall production completion target.